Surf‐Riding Threshold of Ships in Random Seas. Issue 1 (December 2013) - Dostal, Leo; Kreuzer, Edwin
Abstract A possible stability failure in ship dynamics is surf‐riding of the ship in waves followed by broaching‐to. In order to exclude broaching one thus seeks to prevent the ship from surf‐riding. We analyze the surf‐riding problem of a ship in random seas as a weakly perturbed Hamiltonian system, where the excitation owing to irregular sea waves is modeled as a Gaussian process. Then, an approximation of the probability of surf‐riding in irregular sea waves is obtained using the stochastic Melnikov's method, by which means transitions from the asymmetric periodic surging motion to the surf‐riding equilibrium are identified. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)